Sistim Pendukung Keputusan Menentukan Volume Produksi Keripik Tempe Menggunakan Metode Simplek - Susanti, Evi Yulia (AI Society & STMIK Indonesia, 2022)
Tempe can be processed to be used as a variety of dishes and snacks. Tempe chips are processed tempeh made from the main raw material of tempe which is thinly sliced ​​then seasoned and then fried until it has a crunchy texture. Tempe chips have become a business opportunity for Rimbo Ilir, Tebo Regency, Jambi Province with four flavors, Balado, cheese, BBQ and original flavors. The purpose of this study is to help the manager determine the production volume of tempeh chips according to the flavor variant in order to get the expected profit and minimize losses. The method used in this study is linear programming simplex method, using this method the manager is advised to produce tempe chips with Balado flavor of 18,225 pcs and cheese flavored with 6,795 pcs, with a profit of Rp. 24,493. From the sensitivity analysis, it does not mean that BBQ and cheese flavors should not be produced, but that they have a maximum production limit, for BBQ flavors a maximum of 6,286 pcs and original flavors 5,744 pcs.